Praktik Keagamaan Budak Kristen di Batavia Abad XVII dan XVIII - Laksono, Leonard Bayu (Jurnal Sejarah Citra Lekha, 2025)
Slaves have been part of the social structure of 17th-century Batavia since its inception. The multi-ethnic and multi-religious slaves, who encountered Christian Europeans, shaped social life, particularly the religious aspects. This study aims to demonstrate the spiritual practices (Christian) imposed on slaves in 17th- and 18th-century Batavia. This study applies historical research methods using classical sources from the Protestant Church (Gereformeerde Kerk) in the books De Gereformeerde Kerken in Nederland and De Protestantsche Kerk in Nederlandsch-Indië. The results of this study show that slaves owned by Christians continued to fulfill their status and function as economic pillars of Batavia's society. On the other hand, slaves also received equal rights in the implementation of their religious practices. Slaves in Batavia converted to Christianity and freedman due to the Calvinist teachings internalized by the Protestant Church during this period, which proclaimed the equality and freedom of slaves. The slaves who became the personal property of Christian masters were those who lived out their domestic duties and activities. Christian slaves were provided with Christian instruction and moral standards to receive complete spiritual care, including the Sacraments of Baptism and Holy Communion. Therefore, the phenomenon of slavery in Batavia was not only a socio-economic issue but also raised Christian ethical-moral issues.